Failure prediction of high-capacity electrode materials in lithium-ion batteries - Wang, C.; Ma, Z.; Wang, Y.; Lu, Chunsheng (The Electrochemical Society, Inc, 2016)
The large volume change during lithium-ion insertion/extraction leads to huge stress and even failure of active materials. To well understand such a problem, the two-phase lithiation process of film and hollow core-shell electrodes is simulated by using a non-linear diffusion lithiation model. The dynamic evolution of lithium-ion concentration and diffusion-induced stress are obtained. Based on the dimensional analysis, a phase diagram is determined to demonstrate the relationship between critical failure, structure dimensions and mechanical properties. As a case study, the critical state of charge in Sn films are measured and compared with theoretical results.